ABA Type Amphiphiles with Poly(2‐benzhydryl‐2‐oxazine) Moieties: Synthesis, Characterization and Inverse Thermogelation. Issue 17 (2nd August 2021) - Hahn, Lukas; Keßler, Larissa; Polzin, Lando; Fritze, Lars; Forster, Stefan; Helten, Holger; Luxenhofer, Robert
Abstract: Thermoresponsive polymers are frequently involved in the development of materials for various applications. Here, polymers containing poly(2‐ benzhydryl‐2‐oxazine) (pBhOzi) repeating units are described for the first time. The homopolymer pBhOzi and an ABA type amphiphile comprising two flanking hydrophilic A blocks of poly(2‐methyl‐2‐oxazoline) (pMeOx) and the hydrophobic aromatic pBhOzi central B block (pMeOx‐ b ‐pBhOzi‐ b ‐pMeOx) are synthesized and the latter is shown to exhibit inverse thermogelling properties at concentrations of 20 wt.% in water. This behavior stands in contrast to a homologue ABA amphiphile consisting of a central poly(2‐benzhydryl‐2‐oxazoline) block (pMeOx‐ b ‐pBhOx‐ b ‐pMeOx). No inverse thermogelling is observed with this polymer even at 25 wt.%. For 25 wt.% pMeOx‐ b ‐pBhOzi‐ b ‐pMeOx, a surprisingly high storage modulus of ≈22 kPa and high values for the yield and flow points of 480 Pa and 1.3 kPa are obtained. Exceeding the yield point, pronounced shear thinning is observed. Interestingly, only little difference between self‐assemblies of pMeOx‐ b ‐pBhOzi‐ b ‐pMeOx and pMeOx‐ b ‐pBhOx‐ b ‐pMeOx is observed by dynamic light scattering while transmission electron microscopy images suggest that the micelles of pMeOx‐ b ‐pBhOzi‐ b ‐pMeOx interact through their hydrophilic coronas, which is probably decisive for the gel formation. Overall, this study introduces new building blocks for poly(2‐oxazoline) and poly(2‐oxazine)‐based self‐assemblies, but additional studies will be needed to unravel the exact mechanism. Abstract : Novel homopolymers and amphiphilic block copolymers comprising the monomers 2‐benzhydryl‐2‐oxazoline and 2‐benzhydryl‐2‐oxazine (BhOzi) are described. While both types of amphiphilic block copolymers form well‐defined spherical micelles in water, only the amphiphilic block copolymer based on BhOzi forms a thermoresponsive hydrogels upon cooling of the aqueous solutions, presumably via increased correlation between the hydrophilic shells of the micelles.